Startle and surprise in helicopter operations: reported prevalence and application of mitigation strategies - Vlaskamp, Daan; Pollitt, Alex; Blundell, James; Landman, Annemarie; Groen, Eric L.; van Paassen, Marinus M. René; Stroosma, Olaf; Mulder, Max (Springer, 2025)
Startle and surprise can impair pilot performance and affect flight safety. This study investigates the prevalence of different startle and surprise events among helicopter pilots, its impact on pilot stress and mental effort and the influence of training background. It also looks at currently used startle mitigation strategies and evaluates the usability of a previously proposed “Aviate, Breathe, Check (ABC)” startle management method (Piras et al. 2023). A survey among 234 helicopter pilots revealed that 96% had experienced impactful startle or surprise events during operations. Scenarios such as disorientation, tail rotor incidents, and flight into instrument meteorological conditions (IMC) were considered particularly stressful. Reported levels of stress and mental effort during startle and surprise events did not differ between pilots with higher and lower experience levels or between pilots with a different training background (military or civilian). Only 38% of pilots indicated they were specifically trained to deal with startle and surprise and only 1% were trained to use a breathing technique. Most pilots (90%) expressed openness to implementing the ABC method and expected benefits from using it. Concerns regarding time constraints in critical situations emerged as the primary objection to adopting this technique. Overall, the findings indicate that the introduction of a startle management method tailored for helicopter operations could significantly enhance safety, especially given the higher accident rates compared to fixed-wing operations. Future research should focus on developing effective training protocols that account for the unique challenges of helicopter flying.
Keywords: Mental workload; CRM; Startle; Rotary; Situational awareness; Impairment; 46 Information and Computing Sciences; 4609 Information Systems; 3 Good Health and Well Being; Human Factors; 5204 Cognitive and computational psychology